Peru : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2012)
Peru's fiscal framework embedded in the Fiscal Responsibility and Transparency Law (FRTL) has proved to be effective in reducing debt. The FRTL embodies some countercyclical elements in response to output or commodity price shocks. The combination of a provision for a moderate deficit on the downside, and a current expenditure cap on the upside, allows for some countercyclical policy. It still has pockets of procyclicality in the face of large shocks to output or commodity prices.